The Impact of a Walk-in Human Immunodeficiency Virus Care Model for People Who Are Incompletely Engaged in Care: The Moderate Needs (MOD) Clinic. (12th December 2022) - Kumbhakar, Raaka G; Budak, Jehan Z; Tao, Yuan; Beste, Jason; Lake, Eve; Navabi, Nazlee; Mose, Eric; Barker, Gwen; Lee, Ji; Hara, Katie; Khosropour, Christine; Dhanireddy, Shireesha; et al.
Abstract: Background: The Moderate Needs (MOD) Clinic in Seattle, Washington provides walk-in primary care for people with human immunodeficiency virus (HIV) who are incompletely engaged in standard care. Methods: We evaluated HIV outcomes among patients enrolled in the MOD Clinic (within group analysis) and, separately, among MOD patients versus patients who were MOD-eligible but did not enroll (comparison group analysis) during January 1, 2018–September 30, 2021. The primary outcome was viral suppression ([VS] viral load <200 copies/mL); secondary outcomes care engagement (≥2 visits ≥60 days apart) and sustained VS (≥2 consecutive suppressed viral loads ≥60 days apart). In the within group analysis, we examined outcomes at time of MOD enrollment versus 12 months postenrollment. In the comparison group analysis, we examined outcomes at the time of MOD eligibility versus 12 months posteligibility. Both analyses used modified Poisson regression. Results: Most patients in MOD (N = 213) were unstably housed (52%) and had psychiatric comorbidities (86%) or hazardous substance use (81%). Among patients enrolled ≥12 months (N = 164), VS did not increase significantly from baseline to postenrollment (63% to 71%, P = .11), but care engagement and sustained VS both improved (37% to 86%, P < .001 and 20% to 53%, P < .001, respectively) from pre-enrollment to 12 months postenrollment. In the comparison group analysis, VS worsened in nonenrolled patients (N = 517) from baseline to 12 months posteligibility (82% to 75%, P < .001). Patients in the MOD Clinic who met criteria for the comparison group analysis (N = 68) were more likely than nonenrolled patients to be engaged in care at 12 months posteligibility (relative risk, 1.29; 95% confidence interval, 1.03–1.63). Conclusions: The MOD Clinic enrollment was associated with improved engagement in care. This model adds to the spectrum of differentiated HIV care services. Abstract : In a controlled analysis, the Moderate Needs (MOD) Clinic—a walk-in care model for people with HIV incompletely engaged in care—improved engagement in care and may have improved viral suppression.